Augmentation of the Inotropic Effects of Dopamine Following Linezolid Administration in an Infant. (August 2016) - Lovett, Marlina E.; Estrada, Maria; Sargel, Cheryl; Tobias, Joseph D.
Although generally safe and effective, one of the unique properties of linezolid is its weak inhibitory effect on monoamine oxidase. As such, it may interact with other medications that act through the adrenergic or serotonergic systems, including selective-serotonin reuptake inhibitors and vasoactive agents. We present a 3-month-old infant who was being treated with dopamine to maintain mean arterial pressure during mechanical ventilation following viral-induced respiratory failure. Hypertension and tachycardia developed during the administration of linezolid on two separate occasions. The physiology of catecholamine metabolism is reviewed including the role of the monoamine oxidase system. The potential interaction between linezolid and vasoactive agents such as dopamine is discussed.